SEARCHING FOR IDENTITY IN TONI MORRISON'S SONG OF SOLOMON - WIDYANINGRUM , NIKEN (2009)
The object of the study is Song of Solomon novel written by American writer, Toni Morrison. This study describes the life of Black American searching for identity to get the value of life. The study employs descriptive qualitative method. The objectives of this study are as follow: to analyze the novel Song of Solomon written by Toni Morrison based on its structural analysis and to analyze Song of Solomon novel based on Sociological approach. The theoretical approach employed in this study is the sociology of the literature which criticizes the relation between the social realities and the literary work. The method used by the writer in this study for collecting data is library research by collecting and celebrating both primary data the novel Song of Solomon and the data taken from words, phrases, sentences, narration and dialogues in the novel and the secondary data are some materials related to the data required. The outcome of the study is as follows: (1) based on structural analysis it is evident that in this novel, Toni Morrison wants to say that identity is a high value in life;(2) based on sociological analysis, this novel shows Toni Morrison's concern with the problems faced by Black people of her time, namely the problem of identity.